2005
DOI: 10.14712/18059694.2018.27
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Deficiency and Goiter Prevalence of the Adult Population in Erzurum

Abstract: SubjectsThe subjects of the study were chosen among the people who were born in Erzurum and still living there. Study sample was drawn through cluster sampling method. Each 39 Summary: It is believed that total goiter prevalence in Turkey is as high as 30.5%. The iodine deficiency is the distinct etiologic factor in the development of goiter. The aim of this study was to determine goiter prevalence and iodine deficiency in adults living in Erzurum (1659 m above sea level) for at least 10 year. The study involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…It is particularly valuable for accurate detection of small goiters in men and women [43]. The reports of understudy patients indicated that thyroid volumes for male and females were higher than normal level [44]. Despite the biochemical evidence of a high risk for Cu, we did not detect any significant relationships between serum Cu and anthropometric status, in hypothyroid patients.…”
Section: Discussioncontrasting
confidence: 70%
“…It is particularly valuable for accurate detection of small goiters in men and women [43]. The reports of understudy patients indicated that thyroid volumes for male and females were higher than normal level [44]. Despite the biochemical evidence of a high risk for Cu, we did not detect any significant relationships between serum Cu and anthropometric status, in hypothyroid patients.…”
Section: Discussioncontrasting
confidence: 70%
“…Akarsu et al [9] have reported the prevalence of goiter as 5.6% in Erzurum, a city in Northeastern Anatolia. The frequency of people with UIC lower than 5µg/dL was 37.6% [9], indicating that this region is an endemic region in terms of iodine deficiency [5]. In this region, Dundar reported a 7.2% rate of preeclamptic pregnancies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Akarsu et al [10] have reported a 5.6% goiter prevalence rate in Erzurum, a city in northeastern Anatolia. The frequency of people with a urinary iodine concentration lower than 5 μg/dl was 37.6% [10], indicating that this is an endemic region in terms of iodine deficiency [11].…”
Section: Introductionmentioning
confidence: 99%